Long Baseline Observations of the Hd 100546 Protoplanetary Disk with Alma - Perez-Marquez, S (Institute of Physics Publishing, 2020)
Using the Atacama Large Millimeter/submillimeter Array, we observed the young Herbig star HD 100546, host to a prominent disk with a deep, wide gap in the dust. The high-resolution 1.3 mm continuum observation reveals fine radial and azimuthal substructures in the form of a complex maze of ridges and trenches sculpting a dust ring. The 12CO(2-1) channel maps are modulated by wiggles or kinks that deviate from Keplerian kinematics particularly over the continuum ring, where deviations span 90° in azimuth, covering ∼5 km s-1. The most pronounced wiggle resembles the imprint of an embedded massive planet of at least 5 M Jup predicted from previous hydrodynamical simulations. Such a planet is expected to open a deep gap in both gas and dust density fields within a few orbital timescales, yet the kinematic wiggles lie near ridges in the continuum. The lesser strength of the wiggles in the 13CO and C18O isotopologues show that the kinematic signature weakens at lower disk heights, and suggests qualitatively that it is due to vertical flows in the disk surface. Within the gap, the velocity field transitions from Keplerian to strongly non-Keplerian via a twist in position angle, suggesting the presence of another perturber and/or an inner warp. We also present Very Large Telescope/SPHERE sparse aperture masking data that recover scattered light emission from the gap s edges but show no evidence for signal within the gap, discarding a stellar binary origin for its opening. © 2020. The American Astronomical Society. All rights reserved..